Studies in econometrics, time series, and multivariate statistics - Karlin, Samuel, 1923-2007; Amemiya, Takeshi; Goodman, Leo A.; Anderson, T. W. (Theodore Wilbur), 1918-2016 (Academic Press, 1983)
Studies in Econometrics, Time Series, and Multivariate Statistics.